The International Club of San José and fin de siècle’s enlightened culture - Santamaría Montero, Leonardo (2018)
The “International Club”, later named “International Club of Costa Rica”, was the capital’s most important cultural association at the end of the 19th century. This private group was created as a meeting point for the most “enlightened” citizens; a place where they shared their time for entertainment and business purposes. This research is introductory so in this paper: it explores the antecedents of the International Club, identifies its different locations, analyses its 1884 statutes, reviews a testimony of one of its members and studies two events happened at 1885. We propose that through the systematic study of International Club, and the social activities derived thereof, the Art History and Cultural History of Costa Rica will find in this association an important core of its fin de siècle’s “enlightened culture”.